2021
DOI: 10.1097/md.0000000000024480
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of related risk factors of lung metastasis after laparoscopic radical hysterectomy of cervical cancer

Abstract: To explore the risk factors of lung metastasis in patients after laparoscopic radical hysterectomy (LRH) of cervical cancer (CC). The clinical data of CC patients with clinical stage of IA 1 –IIA 2 diagnosed in our hospital from April 2007 to October 2015 were collected. According to the situation of metastasis, the patients were divided into lung metastasis (n = 73) and non-lung metastasis group (n = 2076). The clinical data were compared between 2 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
3
0
2
Order By: Relevance
“…[15,16] Lung is the main metastasis organ of CC, and the probability of lung metastasis is about 4.16% to 7.70%. [14,17] As expected, lung metastasis was also identified as the powerful prognostic factor for OS and CSS in this study. It has been reported that mCC patients with lung metastasis had a remarkably good prognosis compared with other metastatic sites.…”
Section: Discussionsupporting
confidence: 84%
“…[15,16] Lung is the main metastasis organ of CC, and the probability of lung metastasis is about 4.16% to 7.70%. [14,17] As expected, lung metastasis was also identified as the powerful prognostic factor for OS and CSS in this study. It has been reported that mCC patients with lung metastasis had a remarkably good prognosis compared with other metastatic sites.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, the formation of vascular tumor thrombus has been confirmed to be closely related to distant metastasis and lymph node metastasis (23,24). Up to now, previous studies have confirmed that increased CEA, high TNM staging, peripheral invasion and vascular tumor thrombus were independent risk factors of death in non-small cell lung cancer, supporting our study (18,19,22,23). However, the prognosis of patients with non-small cell lung cancer is affected by many factors, so the predictive value of a single biological indicator on prognosis is limited.…”
Section: Discussionmentioning
confidence: 94%
“…When peripheral invasion occurs, it indicates that the tumor has potential to spread, leading to postoperative recurrence and metastasis, and eventually death (22). Finally, the formation of vascular tumor thrombus has been confirmed to be closely related to distant metastasis and lymph node metastasis (23,24). Up to now, previous studies have confirmed that increased CEA, high TNM staging, peripheral invasion and vascular tumor thrombus were independent risk factors of death in non-small cell lung cancer, supporting our study (18,19,22,23).…”
Section: Discussionmentioning
confidence: 98%
“…However, at the onset of metastasis, the 5-year survival rate decreases to 16.5%. Notably, the occurrence rate of cervical cancer with lung metastasis ranges from 2.2% to 9.1%, with patients exhibiting concomitant lung metastasis experiencing significantly decreased survival rates ( 3 , 4 ). Hence, a comprehensive examination of the pathological features and prognostic factors associated with lung metastasis in cervical cancer patients represents a pivotal concern within the realm of clinical treatment.…”
Section: Introductionmentioning
confidence: 99%